Penerapan Bauran Pemasaran Islam untuk Meningkatkan Omset Penjualan pada Bisnis Kafe Takanagari Sidoarjo - Dimas Tresnanda Lusananta; Ahmad Ajib Ridlwan (Institut Agama Islam Negeri Palopo, 2023)
Analyzing the Islamic marketing mix strategy at the Takanagari cafe in Sidoarjo is the objective chosen by the researcher. This research uses a descriptive qualitative research type by obtaining data using observation, interview, and documentation methods. This study uses primary and secondary data sources. The primary data sources are interviews with cafe owner Takanagari Sidoarjo, employees and consumers. Meanwhile, the secondary data sources are journals or literature on the Islamic marketing mix. Based on the study's results, it can be concluded that the application of the Islamic marketing mix to increase sales turnover by the Takanagari Sidoarjo cafe located in Taman Anggun Sejahtera 3 Sidoarjo Housing is considered to have deficiencies in sharia principles still. Meanwhile, in terms of sales turnover, the Takanagari cafe in Sidoarjo has succeeded in increasing its sales turnover with several supporting factors. It would be a good feeling if the research were conducted by looking for the influence of the marketing mix strategy from an Islamic economic perspective on the level of sales turnover.